Kajian Yuridis Kerjasama Pemerintah Dan Swasta Model BOT (Build Operate Transfer) Sektor Infrastruktur Jalan Di Indonesia - Fajar Kusuma Pratama; Budi Santoso (Notarius, 2022)
AbstractBOT (Build Operate Transfer) is one form of financial cooperation agreement in the development, maintenance and or management. One of its kind is Road Infrastructure / Toll Road. In Indonesia, the State needs a budget / capital to finance infrastructure development in various fields, one of which is Road Infrastructure / Toll Road, but funds owned by the government / State through APBN / APBD are limited, in the sense that it is not yet equal to the amount of budget required for various Infrastructure projects. The approach method used in this article is a normative juridical approach. In this research, it is reviewed from the perspective of written regulations based on a literature study which is secondary data. Therefore, it takes the cooperation of third parties as investors / funders to cooperate with the government on infrastructure projects, on the principle of mutual benefit, in order to meet the financing needs and funding of infrastructure projects so as not to overload or be concentrated on funding using government budget funds ( APBN / APBD).Keywords : BOT; infrastructure; road; regulation; agreementAbstrakBOT (Build Operate Transfer) adalah salah satu bentuk perjanjian hubungan kerjasama pembiayaan dalam pembangunan, pemeliharaan dan atau pengelolaan. Salah satu jenis nya yaitu Infrastruktur Jalan/ Jalan Tol. Di Indonesia, Negara membutuhkan anggaran/ modal untuk pembiayaan pembangunan Infrastruktur di berbagai bidang, salah satu nya adalah Infrastruktur Jalan/Jalan Tol, namun dana yang dimiliki pemerintah/Negara melalui APBN/APBD terbatas, dalam artian belum sebanding dengan jumlah anggaran yang dibutuhkan untuk berbagai proyek infrastruktur tersebut.  Metode pendekatan yang digunakan dalam artikel ini adalah pendekatan yuridis normatif. Pada penelitian ini ditinjau dari segi peraturan-peraturan dan studi kepustakaan.  Hasil dalam artikel ini bahwa dibutuhkan kerjasama dari pihak ketiga selaku investor/ pemberi modal untuk melakukan kerjasama dengan pemerintah pada proyek infrastruktur, dengan prinsip saling menguntungkan, dalam rangka memenuhi kebutuhan pembiayaan dan pendanaan proyek infrastruktur sehingga tidak terlalu membebani atau tertumpu pada pendanaan menggunakan dana anggaran pemerintah (APBN/APBD).Kata kunci: BOT; infrastruktur; jalan; peraturan; perjanjian